Digital Singnature Pada File Dokumen Menerapkan Fungsi Hash Dengan Metode MD5 - Saragih, Ririn (TIN: Terapan Informatika Nusantara, 2021)
Documents that have a digital signature are intended to validate where the data comes from. Digital signature can be done through encryption. The algorithm that is usually used for a digital signature on a document file is the Message Digest (MD5) algorithm which is also a hash function. And it is necessary to do the security and authenticity of the Digital signature on the document file so that it is not easily manipulated by others. The method that suits this problem is to use an algorithm that is usually used to create digital signatures, namely the MD5 algorithm which is a hash algorithm of the MD5 type or direction to get the value. hash is 128 bits long. The MD5 algorithm can be used to check data integrity, create digital signatures on document files and others. A digital signature of the security and authenticity of the document file there is also a hash function in the journal entitled Implementing the MD5 algorithm for document security. By using a one-way hash function, it will generate a message Digest from the original message. Developed from the MD5 algorithm developed by Ron Rivest, accepting input messages of various lengths and generating a 128-bit hash code it has become one of the most widely used hash algorithms. This algorithm is basically made for the security and authenticity of digital signatures in document files, the hash function cannot answer all existing problems such as confidentiality issues.